A novel polyethylene oxide/Dendrobium officinale nanofiber: Preparation, characterization and application in pork packaging. (September 2019) - Zhu, Yulin; Cui, Haiying; Li, Changzhu; Lin, Lin
Highlights: The antibacterial nanofibers based on DOP were explored as antibacterial food packaging. Adipic acid was applied to improve fibrous structure of nanofiber with high DOP content. The adipic acid added nanofiber exhibited better release of DOP. Abstract: This research focused on the fabrication and characterizations of polyethylene oxide (PEO)/ Dendrobium officinale polysaccharide (DOP) antibacterial nanofibers by electrospinning technique. As the DOP contents increased in spinning solutions, viscosity decreased along with the increase in conductivity. The morphology of nanofibers changed from uniform structure to beaded structure with the formation of droplet, thus the thermal, mechanical, chemical and antibacterial properties of nanofiber got worse. After addition of adipic acid in PEO/DOP spinning solutions, viscosity increased obviously, which resulted in the uniform fiber structure even at high DOP content. Consequently, the properties of nanofibers were modified correspondingly, implying better miscibility between PEO and DOP by the aid of adipic acid. Finally, adipic acid added PEO/DOP nanofibers at high DOP content exhibited better antibacterial activity against E. coli on pork samples, without impact on the quality of pork. Hence, this study suggested the feasibility of PEO/DOP nanofiber as packaging material for pork preservation.